Examining the impact of nuclear and renewable energy sources on environmental quality: Testing the EKC and LCC hypotheses for Sweden - Berisha,Drilon; Danielsson,Max (2024)
This study investigates the impacts of nuclear and renewable energy consumption on Sweden’s environmental quality from 1965 to 2022. The study employs an Autoregressive Distributed Lag (ARDL) approach combined with a Bounds test to examine the validity of the Environmental Kuznets Curve (EKC) and Load Capacity Curve (LCC) hypotheses simultaneously. This is conducted within the context of Sweden's ambitious climate and energy policy goals. Unlike previous studies, this study explores how energy consumption, specifically renewable and nuclear energy consumption affect CO2 emissions, Ecological Footprint (EF),and Load Capacity Factor (LCF). Our findings confirm the presence of cointegration among the variables, indicating long-term relationships. The results validate the EKC and LCC hypothesis for CO2, LCF and EF, suggesting that economic growth initially increases environmental degradation, which diminishes as the economy grows. The empirical analysis reveals that the impact of renewable energy consumption is notably stronger in reducing CO2 emissions and EF while increasing LCF compared to nuclear energy, highlighting the effectiveness of using renewable energy sources in Sweden. However, nuclear power is considered an essential complementary source to renewable energy in increasing the rate of reducing greenhouse gas emissions. Our study emphasizes the necessity of utilizing an energy mix of both nuclear and renewable energy to achieve the climate objectives
Keywords: Economic Growth; Environmental Degradation; Environmental Kuznets Curve; Load Capacity Factor; Nuclear Energy; Renewable Energy; Sweden.